New Advances in Proteomics Research Methods of Cancer Stem Cells - LI Ming (Zhongliu Fangzhi Yanjiu, 2018)
Proteomics is an emerging discipline to apply multiple technical approaches for studying the proteomics. It has an ability to identify various kinds of signal transduction complexes and paths in stem cell differentiation. First, various approaches can be taken for obtaining sufficient tumor stem cells required for proteomic analysis; second, it is possible to make use of subcellular isolation technique as a tool of proteomic analysis; moreover, proteomic method can be used for identifying tumor stem cell nonspecific proteins; finally, proteomic method is employed for searching new therapeutic targets. The new stem cell culture technique and the latest-level mass spectrometry enable the research on cancer stem cells to step into a new stage, therefore, the application of proteomics can effectively expound which paths have gotten involved in regulation of cancer stem cell activation and other molecular processes, further identify and search single molecules as biomarkers or therapeutic targets.